ZrO2 supported perovskite activation of peroxymonosulfate for sulfamethoxazole removal from aqueous solution. (July 2022) - Jia, Muhan; Fan, Yan; Sun, Zhirong; Hu, Xiang
Abstract: In this study, A- and B-site doped perovskite La0.5 Sr0.5 Co0.8 Ni0.2 O3 （LSCN) was prepared by sol-gel method. On this basis, ZrO2 supported LSCN used to maintain high catalytic activity while inhibit the leaching of toxic Co ions. Compared with the non-doped LaCoO3, the ZrO2 @La0.5 Sr0.5 Co0.8 Ni0.2 O3 (Z@LSCN82)/PMS system could almost completely degrade SMX in 30 min. In addition, the leaching amount of Co ions was only 0.303 mg L −1 . Free radical quenching experiments and electron paramagnetic resonance experiments proved that active species SO4 −, OH and 1 O2 existed in the Z@LSCN82/PMS system, and SO4 − played a major role. Besides, the catalyst had high efficiency for SMX degradation in a wide pH range. In addition, co-existing anions in water such as HPO4 − and Cl − also showed slight inhibition of the system. It was indicated that the Z@LSCN82/PMS system had huge potential applications for practical wastewater treatment. Graphical abstract: Image 1 Highlights: ZrO2 @La0.5 Sr0.5 Co0.8 Ni0.2 O3 /PMS system had the remarkable effect on SMX removal. ZrO2 as a carrier effectively reduced Co ions leaching from perovskite. Ni/Co bimetallic system had higher catalytic activity than monometallic system. SO4 . − and 1 O2 were the main active species for SMX degradation.